"Can you take me higher?": Normative thresholds for air quality in the Salt Lake City Metropolitan area. (15th March 2019) - Zajchowski, Chris A. B.; Brownlee, Matthew T. J.; Blacketer, Michael; Rose, Jeff; Rumore, Danya L.; Watson, Jason; Dustin, Daniel L.
Abstract: Urban-proximate protected areas provide metropolitan residents with a variety of benefits. We explored the pursuit of clean air by winter outdoor recreationists who live in the Salt Lake City metropolitan area of northern Utah, a region that experiences seasonal air pollution events. To better understand how air quality in the Salt Lake Valley affects winter outdoor recreation in the nearby Uinta-Wasatch-Cache National Forest (UWCNF), we employed qualitative interviews ( n = 14) and a norms-based thresholds questionnaire ( n = 380). Results suggest that degraded metropolitan air quality serves as an impetus for winter outdoor recreation in the UWCNF and, at the same time, disproportionately displaces certain recreationists from outdoor pursuits. Participants' normative transit behaviors are discussed, as are the effects of existing air quality conditions on self-reports. These results help illustrate air quality is a viable indicator of overall outdoor recreation quality in the UWCNF and likely in other urban-proximate protected areas.